Implementasi Akuntabilitas dan Transparansi Pada Pelayanan Publik di Kelurahan Pondok Kelapa Jakarta Timur Tahun 2020 - Putri Salma Pratiwi; Sari Ningsih (PANDITA : Interdisciplinary Journal of Public Affairs, 2022)
Good governance practices require transparency in the overall process of governance. Government that is effective, transparent and accountable to its citizens is a top priority for the Government of Indonesia. With various other accountability and supervisory institutions, including the media, to maintain and deepen reform efforts and create anti- corruption institutions that are more transparent, high-performance and responsive to the needs of citizens. This research uses qualitative research methods with interview data collection techniques, observation and documentation. The results of this study indicate that the Pondok Kelapa Village Office has carried out its responsibilities according to Pergub number 152 of 2019 then for transparency it has been stipulated in the SKPD.